Application of Contextual Learning Model to Improve Students' Problem Solving Ability - Herwendi, Ayi (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to enhance the problem-solving abilities of Class VIII students at MTS Negeri Bekasi in the subject of Ranked Numbers. Using Classroom Action Research developed by Kemmis & McTaggart, the study followed four stages: planning, acting, observing, and reflecting, conducted over two cycles with each cycle comprising two meetings. The subjects were 35 Class VIII students. Data was collected through observations, tests, and questionnaires, focusing on the learning outcomes and processes using contextual learning models. The findings indicate that the application of contextual learning models significantly improved students' problem-solving skills. Observations revealed that students could analyze and interpret data from frequency distribution tables and histograms and solve related problems effectively. The problem-solving ability test results showed an improvement from cycle I, where the average score was 77.43 with a completeness percentage of 77.14%, to cycle II, where the average score increased to 82.14 with a completeness percentage of 94.29%. Therefore, the implementation of contextual learning models successfully enhanced the problem-solving skills of students in the Ranked Numbers topic